2016
DOI: 10.2220/biomedres.37.293
|View full text |Cite
|
Sign up to set email alerts
|

<b>Response to light compressive force in human cementoblasts </b><i><b>in </b></i><i><b>vitro </b></i>

Abstract: The objective of this study is to investigate the responses of human cementoblasts to light compressive force in vitro. A human cementoblast cell line (HCEM) was loaded for 12 h by mounting coverslips (0.25 gf/cm 2 ). The coverslips were removed and the cells were cultured for up to 21 days. Cells without glass loading were used as controls. Cell growth, morphological changes, and the mRNA expression of RUNX2, ALP, WNT5A and SPON1 were investigated. No significant differences were observed in cell numbers betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…, Matsunaga et al . ). In the present study, the results of alizarin red staining showed that mineralization increased in the high pH medium compared to the pH 7.6 medium and was inhibited by the TRPA1 antagonist HC030031.…”
Section: Discussionmentioning
confidence: 97%
“…, Matsunaga et al . ). In the present study, the results of alizarin red staining showed that mineralization increased in the high pH medium compared to the pH 7.6 medium and was inhibited by the TRPA1 antagonist HC030031.…”
Section: Discussionmentioning
confidence: 97%
“…The compressive forces applied ranged from 0.25 g/cm 2 to 3 g/cm 2 in previous studies. 5,13 Since root resorption occurs in orthodontic treatment with light force as well, the response of cementoblasts under appropriate compressive force instead of heavy force was investigated. To avoid pathological damage of cementoblasts, the force magnitude was set at 1.5 g/ cm 2 for 8 hours, and the cell viability and apoptosis assays confirmed the absence of significant increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cementogenesis was inhibited under compression as indicated by ALP staining and cementoblast-related gene expression, consistent with previous studies. 3,5 External root resorption results from abnormal cementum remodeling. Thus, compression decreases cementoblastic function and subsequently induces root resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, OPN is proven as being decreased after up to 24 hours in the same compressive conditions 62 . To conclude, cementogenesis is strongly affected by compressive forces 66 67 whereby it remains to be elucidated if there are tissue-specific molecular mechanisms involved in orthodontic root repair 6 . Nevertheless, these results potentially provide new evidence on the mechanism of pathogenesis of root resorption and may offer molecular targets for the preventive treatment of this undesirable outcome 62 .…”
Section: Influence Of Mechanical Loading On Gene Expressionmentioning
confidence: 99%